Perspectives on Reproductive Health Education among Javanese Parents - Widjanarko, Bagoes; Indraswari, Ratih; Kusumawati, Aditya; Handayani, Novia (Kesmas, 2022)
This study aimed to investigate the perspectives of reproductive health education among Javanese parents of children aged 9-11 years. This cross-sectional study was conducted with 12,306 parents in Semarang City, Central Java Province, Indonesia, using a purposive sampling technique. Some parents agreed that reproductive health education at home was unnecessary (29.5%), taboo (45%), difficult (73.1%), and awkward (41.5%). Most parents (72.7%) were not transparent in providing reproductive health information to their children by using other terms to name the genitals, considering the politeness aspect. Good practices of providing reproductive health information are slightly more common in mothers (54.2%), unemployed parents (52.9%), those with a higher education level (69.5%), and those with a family income above the regional minimum wage (59.8%). As many as 76.9% of parents intensely monitor their children; however, 60.63% of parents have poor communications with their children. Parents believe that reproductive health information is essential for their children, but parents find the topic difficult with their children due to taboos and awkward feelings. Accordingly, the Indonesian Ministry of Health should empower parents to discuss reproductive health issues with their children openly.